1988
DOI: 10.1007/bf01745519
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipoprotein Lp(a) concentrations are not influenced by an HMG CoA reductase inhibitor

Abstract: The recent elucidation of the structure of apo(a), the characteristic apoprotein of the lipoprotein Lp(a), has revealed a high homology to human plasminogen [6, 8]. This similarity provides a tentative link between the plasma lipoproteins and the clotting system and may give further insight into the role of Lp(a) in atherosclerosis [2]. Numerous studies have demonstrated a strong association between high levels of Lp(a) and coronary heart disease [1, 3, 10]. Furthermore, there is an additive effect of LDL and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
4
5

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(40 citation statements)
references
References 11 publications
1
30
4
5
Order By: Relevance
“…In one family, an FH heterozygote and his FH homozygote daughter, each with apo(a) phenotype 51/48, there appeared to be a possible gene dosage relationship between the defective LDL receptor allele and plasma Lp(a) concentration. However, an unaf- (26), and secondly, early studies on the turnover of Lp(a) in human subjects have suggested that Lp(a) concentration in plasma correlates strongly with its production rate but not with its fractional catabolic rate (27). In a recent study, we also observed no difference in the fractional catabolic rate for Lp(a) between a group ofnormal and FH heterozygotes with matched apo(a) phenotype (28).…”
Section: Resultscontrasting
confidence: 40%
“…In one family, an FH heterozygote and his FH homozygote daughter, each with apo(a) phenotype 51/48, there appeared to be a possible gene dosage relationship between the defective LDL receptor allele and plasma Lp(a) concentration. However, an unaf- (26), and secondly, early studies on the turnover of Lp(a) in human subjects have suggested that Lp(a) concentration in plasma correlates strongly with its production rate but not with its fractional catabolic rate (27). In a recent study, we also observed no difference in the fractional catabolic rate for Lp(a) between a group ofnormal and FH heterozygotes with matched apo(a) phenotype (28).…”
Section: Resultscontrasting
confidence: 40%
“…Drugs like bile acid sequestrants, niacin, or fibrates when used alone have been attended by mixed results (75). The same applies for HMGCoA reductase inhibitors (39,40). In fact, in a recent study, lovastatin (41) has been reported to raise Lp(a) in -30% ofthe cases, suggesting that this HMGCoA reductase inhibitor might increase the hepatic synthesis of Lp(a).…”
Section: Therapeutic Considerationsmentioning
confidence: 88%
“…This, however, has not proven to be the case. For instance, 3-hydroxy-3-methylglutaryl coenzyme A (HMGCoA) reductase inhibitors have been shown either to have no significant effect (39,40) or in one case, to raise plasma Lp(a) levels (41).…”
Section: Genetics Ofapo(a)mentioning
confidence: 99%
See 1 more Smart Citation
“…These drugs have proven to be extremely effective in lowering plasma LDL and apo-B levels presumably through inhibition of intracellular cholesterol synthesis concomitant with an increase of the LDL receptors in the liver [97]. Although Lp(a) and LDL are very similar especially concerning the content of cholesterol, inhibitors of HMG-CoA-reductase, the regulating enzyme of cholesterol biosynthesis, show no influence [98,99], only modest reduction of about 10% [100,101] or even an increase of serum Lp(a) levels [102]. Altogether the limited magnitude of decrease of Lp(a) by HMG-CoA-reductase inhibitors confirms the assumption that the LDL-receptor does not seem to play a major role in Lp(a) clearance from plasma [103].…”
Section: Lp(a) and Lipid Lowering Drugsmentioning
confidence: 99%